PROTECTION AND REHABILITATION FOR WOMEN VICTIMS OF VIOLENCE ACCORDING TO INDONESIAN LAW (STUDY ON CENTRAL JAVA GOVERNMENT'S HANDLING THROUGH KPK2BGA) - Ani Purwanti (Fakultas Hukum, Universitas Diponegoro, 2017)
Based on the report of Indonesia’s National Commission of Women Rights, the data of violence against women in 2017 are distributed as 10205 cases of domestic violence (75%), 3092 cases in community level (22%), and 305 cases in nation sphere (3%). Domestic violence is the most occurred violence with 4281 cases of physical abuse (42%), followed by 3495 cases of sexual abuse (34%), 1451 cases of psychological abuse (14%), and 978 cases of economic abuse (10%). There are 3092 cases of violence in community level, where sexual abuse is placed in the first rank with 2.290 cases (74%), followed by physical abuse with 490 cases (16%), psychological abuse with 83 cases (3%), violence to migrant labor with 90 cases (3%), and trafficking with 139 cases (4%). The data in Central Java since 2014 until April 2017 noted 5881 victims of violence, consisting of 4724 female and male victims. The data showed that there are 5163 male and 425 female offenders in the violence cases.The fulfillment of the rights for women to get the protection and rehabilitation, especially to get quality, comprehensive, and continuous rehabilitation is urgently required. The regulation to protect and rehabilitate women as the victims of violence exists, although the implementation is not enough.This research used socio-legal approach; an approach overviews the legal and social aspect in observing and finding solution related to the problems in this research.Legal protection to women as the victims of violence exists in the Law and Regulation in Indonesia (Law of Domestic Violence, Law of Trafficking, Law of Victim and Witnesses Protection), while the rehabilitation to violence against women includes medical services, legal aid services, legal enforcement services, legal re-socialization, shelter service, home security services, and counselling services.